Descriptions of two new species of Cyrtodactylus Gray 1827 (Squamata : Gekkonidae) endemic to southern Vietnam - van Tri, Ngo; Bauer, Aaron M. (Zootaxa, 2008)
Two new species of the gekkonid lizard genus Cyrtodactylus Gray, 1827 are described on the basis of voucher specimens collected in isolated mountains separated from the Truong Son Mountain Range, southern Vietnam. Both species were collected from shallow caves, as have been many of the recently described Cyrtodactylus from across Southeast Asia. Both species, C. takouensis sp. nov. from Ta Kou Nature Reserve, Binh Thuan Province and C. huynhi sp. nov. from Chua Chan Mountain, Dong Nai Province, are characterized by a small number of enlarged femoral scales separated from the precloacal scales by a large diastema. They may be distinguished from one another and from all other congeners by differences in rows of tubercles and ventral scales, subcaudal scalation and dorsal color pattern. These new taxa bring the number of currently recognized Cyrtodactylus species in Vietnam to twelve.